Maxillary molar distalization with aligners in adult patients: a multicenter retrospective study - Ravera, Serena; Castroflorio, Tommaso; Garino, Francesco; Daher, Sam; Cugliari, Giovanni; Deregibus, Andrea (Progress in orthodontics, 2016)
Background The aim of the present study was to test the hypothesis that bodily maxillary molar distalization was not achievable in aligner orthodontics. Methods Forty lateral cephalograms obtained from 20 non-growing subjects (9 male, 11 female; average age 29.73 years) (group S), who underwent bilateral distalization of their maxillary dentition with Invisalign aligners (Align Technology, Inc., San José, CA, USA), were considered for the study. Skeletal class I or class II malocclusion and a bilateral end-to-end class II molar relationship were the main inclusion criteria. Cephalograms were taken at two time points: (T0) pretreatment and (T2) post-treatment. Treatment changes were evaluated between the time points using 39 variables by means of paired t test. The level of significance was set at P < 0.05. Reproducibility of measurements was assessed by the intraclass correlation coefficient (ICC). Results The mean treatment time was 24.3 ± 4.2 months. At the post-treatment point, the first molar moved distally 2.25 mm without significant tipping ( P = 0.27) and vertical movements ( P = 0.43). The second molar distalization was 2.52 mm without significant tipping ( P = 0.056) and vertical movements ( P = 0.25). No significant movements were detected on the lower arch. SN^GoGn and SPP^GoGn angles showed no significant differences between pre- and post-treatment cephalograms ( P = 0.22 and P = 0.85, respectively). Conclusions Aligner therapy in association with composite attachments and class II elastics can distalize maxillary first molars by 2.25 mm without significant tipping and vertical movements of the crown. No changes to the facial height were revealed.